2012
DOI: 10.1002/ijc.27332
|View full text |Cite
|
Sign up to set email alerts
|

Active‐specific immunotherapy of human cancers with the heat shock protein Gp96—revisited

Abstract: The passive administration of specific antibodies that selectively target tumors is a well-known strategy in cancer treatment. Active immunotherapy using peptide vaccines, in contrast, is expected to induce specific, cytolytic T cells in the patient, which react against tumor antigens and destroy malignant cells. Although several concepts exist, the identification and low immunogenicity of tumor-specific peptides remain a serious problem. Heat shock proteins (HSPs), notably glycoprotein (Gp) 96, are of special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 167 publications
(183 reference statements)
0
32
0
1
Order By: Relevance
“…Consequently, gp96-peptide complexes extracted from cancer cells harbor tumor-specific peptides and are immunogenic, offering a tool for active immunization against the tumor (13)(14)(15)(16)(17). Therefore, immunologists speculate that every preparation of gp96-associated peptide pool is different.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, gp96-peptide complexes extracted from cancer cells harbor tumor-specific peptides and are immunogenic, offering a tool for active immunization against the tumor (13)(14)(15)(16)(17). Therefore, immunologists speculate that every preparation of gp96-associated peptide pool is different.…”
Section: Resultsmentioning
confidence: 99%
“…Although vaccination of lethally irradiated cancer cells expressing autologous secretory GRP94 fusion proteins protected mice from primary tumour growth and metastasis 158 , vitespen, a GRP94-peptide complex that was purified ex vivo from individual patient's tumour cells showed variable immunogenicity and overall limited efficacy in clinical trials, with clinical responses only in certain patient subsets 159-161 . Recent studies showed that low dose of GRP94 immunization activated cytotoxic T lymphocytes with some tumour suppression in mice whereas high dose induced Treg proliferation and immune suppression, in a manner dependent on TLR-mediated NF-κB activation 162 .…”
Section: Targeting Grpsmentioning
confidence: 99%
“…87,88 Although immune correlates were elicited, overall patient survival was relatively unchanged compared with standard of care regimens. 89 Notably, the first successful phase 1 trial using a human allogeneic lung cancer cell line engineered to secrete gp96-Ig was recently completed.…”
Section: Discussionmentioning
confidence: 99%